Korelasi waktu relaksasi magnetic (t1) dan (t2) dalam nmr dengan .kadar protein pada ikan mia merah oleh variasi waktu pendiaman dan dosis radiasi sinar gamma (y)=Correlation the Magnetic Relaxation Time in NMR (T1 and - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1998)
The longitudinal (TO and transverse (T2) magnetic relaxation time of red nila fish have been measured using pulsed NMR technique, while the protein concentration have been measured using mikro Kjeldhal method. The propose of the research is to study the relationship of longitudinal (Ti) and transverse (T2) relaxation time and protein contained . in the sample due to variation of enduring time, cooling time, and radiation dosage. In measuring T, relaxation time, the 180° - ti - 90° pulsed method has been used, while for T2 relaxation time 90° - T - 180° pulsed method has been used with Minispec P.20 NMR. The result showed exponential relation between T, and T2 to the variation of enduring time and radiation dosage. The relation between protein concentration (tcp) in the sample not irradiated to the magnetic relaxation time T1 as well as T2 , did not show any correlation, but for irradiated fish showed a linear correlation.